Impact of Physical Activity on the Aggressiveness, Deviant Behavior and Self-esteem with School Children Aged 11-15 - Georgi Georgiev; Serjozha Gontarev (Journal of Anthropology of Sport and Physical Education)
Comprehension of factors responsible for reduction of physical activities with adolescents is of a primary importance for an effective development of programs and strategies in promoting the physical activity among this population group. The aim of the present research is the explore impact of physical and sports activities on the aggressive, deviant behavior and self-confidence among schoolchildren aged from 11 to 15. The research was conducted on a sample of 177 Macedonian adolescents from several primary schools in the city of Skopje. More scales of assessing physical activity, sedentary habits, self-confidence and behaving aggressively and in a deviant way were applied for the purposes of the present research. The results obtained from the research are statistically processed and each variable is with individually calculated basic descriptive statistic, while the relation between the applied variables is determined by the use of Pearson’s coefficient of correlation (R). On the base of the obtained data a conclusion can be drawn that there is no statistically significant relation between physical activity and the total or individual types of aggressiveness, deviant behavior and self-confidence. There is a statistically significant positively low correlation between the times spent at the computer desk on work days and physically manifested aggressiveness, and there is statistically significant negative low correlation between the time spent studying and deviant behavior within the whole group of respondents.